Meningkatkan Prestasi Belajar Pendidikan Agama Katolik di SMA Negeri Dengan Media Film - V. Kriswdiatma Tjahja Hernawa; Mulyoto Mulyoto; Djono Djono (Teknodika, 2018)
This research is aimed to know: 1) increase learning Outcomes of Catholic religion education by using film media; 2) increase the learning process; 3) increase students’responses to use of film media in learning of Catholic religion education. This research is Classroom Action Research done in two cycles. The research is done at SMA Negeri Sukoharjo. The Object of the research is the improvement of learning outcomes, the quality of learning proses with film media and student responses using film media.  The technic of collecting data used observation, questionnaire, and objective test. Data obtained from the test method and quiestionnaire method were analyzed by quantitative descriptive technique and documentation and observation was analiyzed by qualitative descriptive. The result of research shows (1) An increase in the average score of the class score in test from 63 in cycle 1 to 83 in cycle 2. (2) film media Yohanes Paulus 2 can provide inspiration and cultivevate student activeness in the lerning process. (3) students responded verry positively tonthe use of film media. Based on the results of research, the researchers concluded that the use of film media in SMA Sukoharjo can improve learning outcomes and student’s activeness in the learning process.